Functions of Rhetorical Questions with Words ГДЕ [gdye], КУДА [kuda] and ОТКУДА [otkuda] - E. B. Stepanova (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
This article is devoted to the secondary functions of rhetorical questions with interrogative adverbs где , куда and откуда . It is shown for the first time that these rhetorical questions can be used to substantiate the speaker’s opinion, support the addressee’s words, express refusal, objection or evaluate the addressee’s action as inappropriate. Particular attention is paid to the semantic specificity of rhetorical questions with these words: when performing the function of justification, for example, rhetorical questions with the words где , куда and откуда can preserve the spatial meaning and signal that there is no place that meets the conditions, or it exists in a single version, or there are many such places. It is also proved that, in addition to spatial meanings, rhetorical questions with these words can express different figurative meanings: purpose of action ( куда ); method of action ( где , откуда ); source of information ( откуда ); the reason for the appearance of a new situation ( откуда ). Also rhetorical questions are presented, in which the words где and куда can undergo desemantization.